Minimally invasive access type related to outcomes of sutureless and rapid deployment valves. (26th June 2020) - Andreas, Martin; Berretta, Paolo; Solinas, Marco; Santarpino, Giuseppe; Kappert, Utz; Fiore, Antonio; Glauber, Mattia; Misfeld, Martin; Savini, Carlo; Mikus, Elisa; Villa, Emmanuel; Phan, Kevin; et al.
Abstract: OBJECTIVES: Minimally invasive surgical techniques with optimal outcomes are of paramount importance. Sutureless and rapid deployment aortic valves are increasingly implanted via minimally invasive approaches. We aimed to analyse the procedural outcomes of a full sternotomy (FS) compared with those of minimally invasive cardiac surgery (MICS) and further assess MICS, namely ministernotomy (MS) and anterior right thoracotomy (ART). METHODS: We selected all isolated aortic valve replacements in the Sutureless and Rapid Deployment Aortic Valve Replacement International Registry (SURD-IR, n  = 2257) and performed propensity score matching to compare aortic valve replacement through FS or MICS ( n  = 508/group) as well as through MS and ART accesses ( n  = 569/group). RESULTS: Postoperative mortality was 1.6% in FS and MICS patients who had a mean logistic EuroSCORE of 11%. Cross-clamp and cardiopulmonary bypass (CPB) times were shorter in the FS group than in the MICS group (mean difference 3.2 and 9.2 min; P  < 0.001). Patients undergoing FS had a higher rate of acute kidney injury (5.6% vs 2.8%; P  = 0.012). Direct comparison of MS and ART revealed longer mean cross-clamp and CPB times (12 and 16.7 min) in the ART group ( P  < 0.001). The postoperative outcome revealed a higher stroke rate (3.2% vs 1.2%; P  = 0.043) as well as a longer postoperative intensive care unit [2 (1–3) vs 1 (1–3) days; P  = 0.009] and hospital stay [11 (8–16) vs 8 (7–12) days; P  < 0.001] in the MS group than in the ART group. CONCLUSIONS: According to this non-randomized international registry, FS resulted in a higher rate of acute kidney injury. The ART access showed a lower stroke rate than MS and a shorter hospital stay than all other accesses. All these findings may be related to underlying patient risk factors.